Upaya Preventif Insiden Penyakit Akibat Kerja Pada Perusahaan Industri Baterai - Naely Rahma; Deka Bagus Binarsa; Andri Catur Jatmiko (Perhimpunan Dokter Kedokteran Komunitas dan Kesehatan Masyarakat Indonesia (PDK3MI), 2022)
The issue of Occupational Safety and Health (K3) in general in Indonesia is still often neglected. Occupational disease is an important concern because it appears in the long term so that disease prevention efforts must be carried out. Indonesia is a major player in the nickel-based industry in the world. Indonesia has several battery factories that have been running for a long time with nickel as raw material. This study aims to understand the efforts to prevent occupational diseases in the battery industry. This research is a systematic review of articles obtained through manual search engines from Google Scholars, Proquest, PubMed, Research Gate and has been published nationally and internationally in 2015-2020 and obtained from 30 scientific articles. Diseases caused by Employment is still a major problem in various industrial fields. The causative factors are also of various kinds due to environmental factors, biology, ergonomics, or from worker factors. There are several preventive measures that can be adjusted to the possibility of occupational diseases that may arise. Nickel is the raw material for making batteries. Workers in the battery industry can experience occupational diseases, including: allergic contact dermatitis, bacterial conjunctivitis, noise-induced hearing loss, Low Back Pain and Carpal tunnel syndrome. Some of the prevention efforts that can be done include: using personal protective equipment, detecting workers who have a history of DKA, maintaining cleanliness and cleanliness of the work environment, using furniture that is in accordance with ergonomic standards and not lifting heavy loads, reducing repetitive stresses. movement and regular exercise.